Pemeliharaan Kesehatan Lansia Aktif dan Sehat melalui “Foot Exercise” sebagai Pencegahan Komplikasi Diabetes Mellitus: Active and Healthy Elderly Health Maintenance through “Foot Exercise” as Prevention of Diabetes Mellitus Complications - Safariyah, Erna; Danismaya, Irawan; Hamzah, Amir; Alamsah, Mustopa Saepul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Diabetes mellitus is one of the chronic diseases with an increasing incidence every year. The increasing number of people with Diabetes Mellitus can be influenced by several factors, such as the economy, lack of knowledge and unhealthy lifestyle, age, and also overweight. Cases of diabetes mellitus in Sukabumi City have increased, including in Lembursitu (9.8%). The solution offered is to maintain health through health education and "foot exercise". Community service is carried out in the work area of the Lembursitu Health Center. The goal of this activity is to improve the health of the elderly by applying a healthy lifestyle and Foot Exercise in daily life. Community Service consists of 2 stages. The first stage is planning and the second stage is implementation. At this stage, conducting health screening and education about healthy lifestyles and foot exercise with simulations and demonstrations. Community service has an impact on partners. The target is the elderly with diabetes mellitus. The increase in knowledge that occurs in the elderly and the prevention of complications has an impact on the health condition. Diabetes mellitus sufferers apply a healthy lifestyle in their lives so that there is an increase in health and quality of life. This also has an impact on the ability to meet daily needs. The follow-up plan is assistance in the implementation of foot exercises so that they can be carried out routinely at least 2 times a week, and involves cadres to make a routine schedule in implementing efforts to prevent complications.